Comparing the efficacy of non-penetrating deep sclerectomy combined with endotrabeculectomy with that of trabeculectomy - I. Ia. Novytskyy; O. V. Levytska (Ukrainian Society of Ophthalmologists, 2022)
Purpose: To compare the clinical efficacy of non-penetrating deep sclerectomy (NPDS) combined with ab interno endotrabeculectomy (ETE) with that of penetrating trabeculectomy for primary open-angle glaucoma (POAG). Material and Methods: Twenty-five patients (25 eyes) that received surgery for POAG were included in the study and divided into two groups based on the type of surgery received: trabeculectomy (13 patients) and NPDS combined with ETE (12 patients). Results: There was a significant difference (a) between preoperative and any postoperative intraocular pressure (IOP) levels, and (b) between preoperative and postoperative mean numbers of ocular hypotensive medications used for either group at any time point of the 12-month follow-up (р < 0.05). In addition, there was no significant difference in IOP between groups (р > 0.05) at any time point. Moreover, there was no significant difference in the number of ocular hypotensive medications used between the groups at any time point. Conclusion: Not only EDE combined with NPDS has at least the same ocular hypotensive effect as that of trabeculectomy for POAG, but it is also advantageous in a low incidence of severe postoperative complications, which may make it a procedure of choice for POAG.